2004
DOI: 10.1002/jso.20156
|View full text |Cite
|
Sign up to set email alerts
|

Two colons‐two cancers: Paradigm shift and clinical implications

Abstract: Embryological and physiological data suggest that proximal (in relation to the splenic flexure) and distal parts of the colon represent distinct anatomical and functional entities. Since 1990, molecular biologists have identified two distinct pathways, microsatellite instability (MSI) and chromosomal instability (CIN), which are involved in the pathogenesis of colon cancer (CC). Thus, a new paradigm has emerged with the discovery that CC is a heterogeneous disease; furthermore recent data have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
228
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(244 citation statements)
references
References 46 publications
10
228
1
5
Order By: Relevance
“…These findings further support previous evidence suggesting that proximal and distal CRC may represent different epidemiological, pathological, genetic, and clinical entities. 23 , 24 Right-sided tumours, often defined as proximal to the splenic flexure, are generally poorly differentiated, diagnosed in more advanced tumour stages, displaying different molecular patterns, and carrying a poorer prognosis than left-sided tumours. 24 , 25 Several studies also demonstrate the importance of taking PTL into account when evaluating treatment response, 26-28 and retrospective analyses from large phase III trials have demonstrated that patients with right-sided tumours have less benefit from the addition of EGFR-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings further support previous evidence suggesting that proximal and distal CRC may represent different epidemiological, pathological, genetic, and clinical entities. 23 , 24 Right-sided tumours, often defined as proximal to the splenic flexure, are generally poorly differentiated, diagnosed in more advanced tumour stages, displaying different molecular patterns, and carrying a poorer prognosis than left-sided tumours. 24 , 25 Several studies also demonstrate the importance of taking PTL into account when evaluating treatment response, 26-28 and retrospective analyses from large phase III trials have demonstrated that patients with right-sided tumours have less benefit from the addition of EGFR-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…55 Two different pathways, microsatellite instability (MSI) and chromosomal instability (CIN), are involved in the pathogenesis of CRC. Tumors originating in the proximal part of the colon carry a better patient prognosis due to a high percentage of MSI-positive lesions, 56,57 whereas distal cancers are more often initiated through the CIN pathway 58 with a potentially worse prognosis. MMP-2, TIMP-3 and TIMP-4 may be of future clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is accumulating evidence suggesting that the right and left colon may be considered as two distinct 'organs' with different embryology, biochemical metabolism and carcinogenesis. 31,32 Although it does not appear simply to be a marker of the right colon itself (as it was negative in flat mucosa regardless of site), it is difficult to address the possibility that MUC6 may highlight right colon polyps regardless of their pathogenesis, because of the distinct segregation of sessile serrated adenomas and hyperplastic polyps in the right and left colon, respectively. However, our series did include five left colonic sessile serrated adenomas that were MUC6-positive, and one right colonic hyperplastic polyp that was MUC6-negative.…”
Section: Discussionmentioning
confidence: 99%